Building a global-oriented talent development system for traditional Chinese medicine: A systematic review - Yue, Du; Azman, Norzaini (Edelweiss Applied Science and Technology, 2025)
This systematic review investigates the current landscape and persistent challenges in developing a globally oriented talent cultivation system for Traditional Chinese Medicine (TCM). Conducted in accordance with PRISMA 2020 guidelines, the review identified 128 initial records, screened 94 studies, and ultimately included 23 for detailed analysis. The findings indicate that TCM international education encounters a range of complex challenges, including cross-cultural knowledge transmission, standardization of professional terminology, development of intercultural competence, adaptation of clinical teaching models, and the establishment of robust quality assurance mechanisms. Although strong policy support and rising global demand have accelerated the internationalization of TCM, the existing training system remains fragmented and insufficiently aligned with international standards. The review concludes that a systematic reconstruction of the TCM talent development framework is imperative, with particular emphasis on integrating disciplinary knowledge, cultural literacy, and competency formation, as well as standardizing clinical instruction and strengthening internationally compatible quality assurance systems. These insights provide both theoretical foundations and practical implications for advancing the global development of TCM education.